Augmented reality, virtual reality, and computer graphics. 4th International Conference, AVR 2017, Ugento, Italy, June 12-15, 2017, Proceedings /: 4th International Conference, AVR 2017, Ugento, Italy, June 12-15, 2017, Proceedings. Part I : (2017) - Unknown
No abstract available